Comprehensive widely targeted metabolomics to decipher the molecular mechanisms of Dioscorea opposita thunb. cv. Tiegun quality formation during harvest - Li An; Yongliang Yuan; He Chen; Meng Li; Jingwei Ma; Juan Zhou; Lufei Zheng; Huan Ma; Zenglong Chen; Chenyu Hao; Xujin Wu (Food Chemistry: X, 2024)
Dioscorea opposita Thumb. cv. Tiegun is commonly consumed as both food and traditional Chinese medicine, which has a history of more than two thousand years. Harvest time directly affects its quality, but few studies have focused on metabolic changes during the harvesting process. Here, a comprehensive metabolomics approach was performed to determine the metabolic profiles during six harvest stages. Thirty eight metabolites with significant differences were determined as crucial participants. Related metabolic pathways including phenylalanine, tyrosine and tryptophan biosynthesis, stilbenoid, diarylheptanoid and gingerol biosynthesis, phenylpropanoid biosynthesis, flavonoid biosynthesis and tryptophan metabolism were the most active pathways during harvest. The results revealed that temperature has a significant impact on quality formation, which suggested that Dioscorea opposita thumb. cv. Tiegun harvested after frost had higher potential value of traditional Chinese medicine. This finding not only offered valuable guidance for yam production, but also provided essential information for assessing its quality.